Atomistic simulations of vibration and damping in three-dimensional graphene honeycomb nanomechanical resonators. (March 2020) - Li, Bing; Wei, Yulan; Meng, Fanchao; Ou, Pengfei; Chen, Yuying; Che, Lei; Chen, Cheng; Song, Jun
Abstract: The vibration characteristics and damping of three-dimensional graphene honeycombs (3DGHs) were studied using molecular dynamics simulations and continuum modeling. Both zigzag and armchair 3DGHs were considered. Longitudinal harmonic excitation was applied on the free end of the cantilever honeycomb along the axial direction. Based on the curves of the vibration responses and the amplitude-frequency characteristic of the 3DGH, it was revealed that the amplitude of vibration response and the resonant frequencies of the 3DGHs were influenced by both the excitation frequency and the amplitude of the excitation force. Moreover, the vibration characteristics of the 3DGHs exhibit spring softening nonlinearity, with greater nonlinearity observed as the exciting force increases. The linear and nonlinear damping of the 3DGHs were further evaluated using the loss factor in the sub-resonant regime under various excitation forces, showing that the 3DGH as a resonator can be excited at higher frequencies of GHz with a small loss factor than graphene and CNT. This study demonstrates the relationships of resonant frequencies and damping with the frequency and amplitude of the excitation force in 3DGHs, providing theoretical foundation for designing 3DGH nanomechanical resonators. Highlights: This study explored vibration characteristics and damping of two types of three-dimensional graphene honeycombs (3DGHs), i.e., zigzag and armchair honeycombs. It would provide theoretical foundation for designing 3DGH nanomechanical resonators. Our findings help gain deep insights into modifying vibration characteristics of 3DGHs through flexible structural tailoring. Enhanced stability and durability could be achieved with a wide range of excitation forces and ultra-high excitation frequencies for 3DGH..